Buckwheat (Fagopyrum esculentum)– a Potential Coarse Grain Crop for Food and Nutritional Security - Sah, Dinesh; Sen, Debashish; Debnath, P. (International Journal of Bio-resource and Stress Management, 2012)
Buckwheat (Fagopyrum esculentum), one of the traditional, underexploited crop having food value, can be grown in harsh climatic condition. Tender shoots, flowers, green leaves, seed and flour of buckwheat is consumed in many ways. The crop can be grown in varied soil and climatic conditions. Buckwheat is a rich source of protein and carbohydrate while crude fat, fiber and minerals content in buckwheat is comparatively higher than common cereal crops. Buckwheat has excellent protein quality in terms of amino acid composition. It contains the high value for lysine (300 mg g-1 N) followed by other cereal grains. It contains considerable amounts of vitamins B1 and B2. It is virtually fat free and total lipids in seed ranged from 1.5-3.7%.